Recent developments in the regulation of cholesterol transport by natural molecules. (29th July 2021) - Tan, Meiao; Ye, Jintong; Zhao, Min; Ke, Xuehong; Huang, Keer; Liu, Huabao
Abstract : The dysregulation of cholesterol metabolism is a high‐risk factor for non‐alcoholic fatty liver disease (NAFLD), dyslipidemia, and atherosclerosis (AS). Cholesterol transport maintains whole‐body cholesterol homeostasis. Low‐density apolipoprotein receptor (LDLR) mediates cholesterol uptake in cells and plays an important role in the primary route of circulatory cholesterol clearance in liver cells. Caveolins 1 is an integral membrane protein and shuttle between the cytoplasm and cell membrane. Caveolins 1 not only plays a role in promoting cholesterol absorption in cells but also in the transport of cellular cholesterol efflux by interacting with the ATP‐binding cassette transporter A1 (ABCA1) and scavenger receptor class B type I (SR‐BI). These proteins, which are associated with reverse cholesterol transport (RCT), are potential therapeutic targets for NAFLD and AS. Many studies have indicated that natural products have lipid‐lowering effects. Moreover, natural molecules, derived from natural products, have the potential to be developed into novel drugs. However, the mechanisms underlying the regulation of cholesterol transport by natural molecules have not yet been adequately investigated. In this review, we briefly describe the process of cholesterol transport and summarize the mechanisms by which molecules regulate cholesterol transport. This article provides an overview of recent studies and focuses on the potential therapeutic effects of natural molecules; however, further high‐quality studies are needed to firmly establish the clinical efficacies of natural molecules.